Synthesis of locust bean gum-based terpolymer bentonite composite: evaluation for indigo carmine adsorption - Badalamoole, Vishalakshi; Abubakar Zauro, Sirajo (International Journal of Advanced Chemistry, 2017)
A terpolymer gel compositeis made up of locust bean gum (LBG), diallyldimethylammonium chloride (DADMAC), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) and bentonite (BNT) was prepared using methylenebisacrylamide (MBA) as crosslinker via microwave irradiation and characterized using FTIR, TGA and SEM techniques. Swelling behavior of the composite was studied under different pH conditions. The composite was also evaluated for adsorption of anionic dye ‘Indigo Carmine’ (IC). The behaviour of the composite was compared with the terpolymer gel without the clay component. The gel showed remarkably higher swelling under neutral pH compared to the composite. The adsorption capacity of the terpolymer gel without clay for Indigo Carmine dyeis also found to be higher (17.36 mg/g) compared to the clay composite (11.99 mg/g). The adsorption data were subjected to three different isotherm models namely; Freundlich, Langmuir and Temkin and were observed to be explained best by Freundlich model. The adsorption of indigo Carmine on the terpolymer gel and the composite is observed to be a second order kinetic process.